Correlation analysis of metabolic syndrome and its components with thyroid nodules - Liu J (Dove Medical Press, 2019)
Jingfang Liu, Chenge Wang, Xulei Tang, Songbo Fu, Gaojing Jing, Lihua Ma, Weiming Sun, Yujuan Li, Dan Wu, Ying Niu, Qianglong Niu, Huiping Guo, Pei SongDepartment of Endocrinology, The First Hospital of Lanzhou University, Lanzhou, Gansu 730000, People’s Republic of ChinaCorrespondence: Jingfang Liu; Xulei TangDepartment of Endocrinology, The First Hospital of Lanzhou University, 1 Donggang West Road, Lanzhou, Gansu 730000, People’s Republic of ChinaTel +86 0 931 835 6470Email ljf824168@126.com xulei_tang@126.comObjective: This study aimed to analyze the relationship between the metabolic syndrome (MetS) and its components with the occurrence of thyroid nodules.Methods: A total of 2719 volunteers from some areas of Gansu Province, China, who participated in the national survey of thyroid diseases and iodine nutrition status (Tide) and diabetes prevalence, were selected. Their height, weight, waist circumference (WC), systolic blood pressure (SBP), and diastolic blood pressure were recorded. The fasting plasma glucose (FPG), 2-h plasma postprandial glucose (2hPG), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and glycosylated hemoglobin (HbA1C) levels were measured. The prevalence of MetS and thyroid nodules was evaluated, and the correlation between each component of MetS and thyroid nodules was studied.Results: The prevalence of MetS and thyroid nodules was 15.4% and 17.2%, respectively. WC, SBP, body mass index, FPG, 2hPG, TG, TC, and thyroid-stimulating hormone levels were significantly higher in the thyroid nodule group. The prevalence of thyroid nodules was significantly higher in the MetS group. A positive correlation was found between the degree of metabolic disorder and the occurrence of thyroid nodules. WC was found to be a risk factor for the occurrence of thyroid nodules. For WC≥90 cm, an increase in the independent variables led to a significant rise in the incidence of thyroid nodules.Conclusion: The prevalence of thyroid nodules was higher in the MetS group. The WC of the MetS components might be an independent risk factor for the occurrence of thyroid nodules.Keywords: metabolic syndrome, risk factors, thyroid nodules, waist circumference